Arabic Pidgins And Creoles - Avram, Andrei (My University, 2020)
The chapter is an overview of eight Arabic-lexifier pidgins and creoles: Turku, Bongor Arabic, Juba Arabic, Kinubi, Pidgin Madame, Jordanian Pidgin Arabic, Romanian Pidgin Arabic, and Gulf Pidgin Arabic. The examples illustrate a number of selected features of these varieties. The focus is on two types of transfer, imposition and borrowing, within the framework outlined by Van Coetsem (1988; 2000;2003) and Winford (2005; 2008).
Keywords: creoles; pidgins; HUMANITIES and RELIGION::Languages and linguistics::Other languages::Arabic language